Development, validity and reliability of the Orofacial Esthetic Scale — Spanish version. Issue 4 (October 2018) - Simancas-Pallares, Miguel; John, Mike T.; Prodduturu, Swati; Rush, William A.; Enstad, Christopher J.; Lenton, Patricia
Abstract: Purpose: To develop a Spanish version of the Orofacial Esthetic Scale (OES-Sp) and to determine its psychometric properties in dental patients. Methods: We performed a validation study for OES development and validation into Spanish. In the development phase, eight individuals participated in the translation process (cross-cultural adaptation) following the PROMIS methodology. In the validation phase, 331 dental patients (age mean ± sd: 42.9 ± 12.3 years, 59 % female) from the HealthPartners dental clinics in Minnesota, USA responded to a survey of Spanish speaking patients ( n  = 540, response rate: 61 %). We first explored dimensionality by means of exploratory factor analysis and scree plot, and then we computed reliability measures with the Cronbach's alpha statistic. Finally, we assessed convergent validity by computing Pearson/Spearman rank correlations between OES-Sp and Oral Health Impact Profile (OHIP)-based orofacial appearance measures. All statistical procedures were performed using Stata v.13 for Windows (StataCorp). Results: Exploratory factor analysis provided evidence that a single factor represents the Spanish OES version. Score reliability was high with Cronbach's alpha statistic of 0.95 (lower limit of the 95 % CI: 0.94). Score validity was sufficient indicated by Pearson and Spearman rank correlations between −0.53 and −0.69 (all 95 % confidence intervals: less than ± 0.10). Conclusions: OES is a valuable instrument to measure the orofacial appearance construct for Spanish-speaking populations. OES was concluded to be unidimensional with excellent score reliability and sufficient convergent score validity when compared with other Orofacial Appearance measures. Our results suggest that OES could be used in Spanish-speaking patients, an important and growing population around the globe.